Type I interferons in host defence and inflammatory diseases - Crow, Mary K.; Ronnblom, Lars (Lupus science & medicine, 2019)
Type I interferons (IFN) can have dual and opposing roles in immunity, with effects that are beneficial or detrimental to the individual depending on whether IFN pathway activation is transient or sustained. Determinants of IFN production and its functional consequences include the nature of the microbial or nucleic acid stimulus, the type of nucleic acid sensor involved in inducing IFN, the predominant subtype of type I IFN produced and the immune ecology of the tissue at the time of IFN expression. When dysregulated, the type I IFN system drives many autoimmune and non-autoimmune inflammatory diseases, including SLE and the tissue inflammation associated with chronic infection. The type I IFN system may also contribute to outcomes for patients affected by solid cancers or myocardial infarction. Significantly more research is needed to discern the mechanisms of induction and response to type I IFNs across these diseases, and patient endophenotyping may help determine whether the cytokine is acting as ‘friend’ or ‘foe’, within a particular patient, and at the time of treatment. This review summarises key concepts and discussions from the second International Summit on Interferons in Inflammatory Diseases, during which expert clinicians and scientists evaluated the evidence for the role of type I IFNs in autoimmune and other inflammatory diseases.